2016
DOI: 10.1007/s00464-016-5148-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lymph node metastasis and long-term outcomes of patients with early gastric cancer after non-curative endoscopic submucosal dissection

Abstract: A detailed assessment of LVI is essential to the pathological evaluation of endoscopically resected specimens. An additional surgical resection should be strongly recommended for patients with LVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 28 publications
5
78
3
Order By: Relevance
“…This result indicates that additional gastrectomy with lymphadenectomy should be performed for lesions with lymphatic invasion. Some similar studies [20, 21] reported that lymphatic invasion was an independent risk factor for LNM in non-curative ER patients. Furthermore, all metastatic nodes were located in the perigastric area close to the primary tumors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result indicates that additional gastrectomy with lymphadenectomy should be performed for lesions with lymphatic invasion. Some similar studies [20, 21] reported that lymphatic invasion was an independent risk factor for LNM in non-curative ER patients. Furthermore, all metastatic nodes were located in the perigastric area close to the primary tumors.…”
Section: Discussionmentioning
confidence: 97%
“…However, this result should be carefully interpreted, because histological analysis demonstrated that the patients who underwent gastrectomy showed significantly higher lymphatic-vascular involvement and deeper submucosal invasion than those followed up without gastrectomy (Table 1), indicating that the patients with these unfavorable histological findings were more frequently selected for additional gastrectomy. Kawata et al [20] and Suzuki et al [21] reported that there was a significant difference in OS between additional surgery and follow-up groups, although disease-specific survival did not differ significantly between the two groups. In patient clinical backgrounds, the follow-up group was significantly older than the additional surgery group, and several patients died of causes other than gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this category, until JGCA guidelines version 4, additional surgery was recommended for all patients as a result of the potential risk of LNM. However, the rate of LNM in such patients was only 5.2%–11.0% . Thus, this recommendation may have been excessive.…”
Section: Management After Er In Each Curability Categorymentioning
confidence: 98%
“…In these patients, endoscopic resection (ER) is currently accepted as a curative treatment meeting the current treatment guidelines . After ER, the risk of lymph node metastasis (LNM) can be assessed based on several factors, including lymphovascular invasion, submucosal invasion, histological type, and size of the tumor, all well‐known risk factors for LNM . Non‐curative ER patients whose cases extend beyond the expanded criteria should receive additional surgery due to the risk of LNM.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐curative ER patients whose cases extend beyond the expanded criteria should receive additional surgery due to the risk of LNM. In patients undergoing additional surgery for non‐curative ER, the LNM rate ranged from 5.7% to 10.4%, even in cases of intramucosal gastric cancer . In these non‐curative ER patients, additional curative surgery should be performed …”
Section: Introductionmentioning
confidence: 99%